Cigarette smoke interacts with amiodarone toxicity in Saccharomyces cerevisiae. Issue 5 (26th November 2022) - Al‐Attrache, Houssein; Halloum, Iman; Hammoud, Lara; El Ghoz, Katia; Abdel‐Razzak, Ziad
Abstract: Amiodarone (AMD) is an antiarrhythmic drug prescribed to treat ventricular tachycardia and fibrillation. However, it causes an unpredictable toxicity (idiosyncratic), which may depend on co‐exposure to pollutants. AMD toxicity involves calcium homeostasis alteration and oxidative stress, which are also affected by cigarette smoke (CS). We investigated the interaction of CS‐condensate (CSC), phenanthrene, and benzo(a)pyrene with AMD toxicity on Saccharomyces cerevisiae . AMD toxicity was reduced by CSC or phenanthrene. Benzo(a)pyrene mildly decreased AMD toxicity on the wild‐type strain, but not on the catalase‐CTT1 mutant. This latter and other mutants in glucose receptor‐GPR1 or calcium transporter‐PMR1 showed lower antagonistic effect to AMD by CSC or phenanthrene relative to the wild type, suggesting roles of oxidative stress, calcium homeostasis, and hexose‐sensing in this interaction. Abstract : Amiodarone (AMD) is an antiarrhythmic drug prescribed to treat ventricular tachycardia and fibrillation. However, it causes an unpredictable toxicity (idiosyncratic), which may depend on co‐exposure to pollutants. AMD toxicity involves calcium homeostasis alteration and oxidative stress, which are also affected by cigarette smoke (CS). We investigated the interaction of CS‐condensate (CSC), phenanthrene, and benzo(a) pyrene with AMD toxicity on Saccharomyces cerevisiae. AMD toxicity was reduced by CSC or phenanthrene. Benzo(a)pyrene mildly decreased AMD toxicity on the wild‐type strain, but not on the catalase‐CTT1 mutant. This latter and other mutants in glucose receptor‐GPR1 or calcium transporter‐PMR1 showed lower antagonistic effect to AMD by CSC or phenanthrene relative to the wild type, suggesting roles of oxidative stress, calcium homeostasis, and hexose‐sensing in this interaction.